The engineer and the plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Stephan Tongo was trained as an engineer in the national training college at Vierzon in France. In the early 1960s, he took up a post in the national railway company of Cameroon, as the manager of rolling-stock maintenance. At home, in the villa...